Association of social isolation and health across different racial and ethnic groups of older Americans - MIYAWAKI, CHRISTINA E. (Ageing Soc, 2014)
Social isolation is a social and public health problem that affects people of all ages, especially elders. Previous studies have found that social isolation across numerous industrialised countries is associated with negative health outcomes. However, it is unknown whether and how this association differs by race/ethnicity and age. To begin to address this gap, this study examines the association of social isolation and physical and mental health among Black, White and Hispanic elders in the United States of America. Building on Cornwell and Waite's perceived isolation and social disconnectedness dimension model of social isolation, the author used multi-stage survey data from a nationally representative sample of 3,005 community-residing adults aged 57–85 from the National Social Life, Health, and Aging Project. Tests for association were conducted on health by age, gender, marital status, education and race/ethnicity separately. Multivariate logistic regressions were used to test the association of social isolation and health exclusively and separately among these three groups. Results showed that social isolation is strongly associated with physical and mental health. Both perceived isolation and social disconnectedness had a significant negative association with physical and mental health among White elders. For Blacks, social disconnectedness is negatively associated with their physical health while perceived isolation had a negative association with mental health. Among Hispanic elders, there seemed to be no association between social isolation and physical health, but a significant negative association was found with their mental health. Despite various associated patterns, however, social isolation overall was associated with health outcomes that were similar across three elder groups. By identifying factors influencing social isolation and health among minority older Americans, this study has relevance to the development of culturally sensitive health-care practice and services, which may be applicable to minority elders in different countries.